Day of the week to tweet: A randomised controlled trial - Mahesh Jayaram; Clive E Adams; Johannes S Friedel; Eimear McClenaghan; Alan A Montgomery; Maritta Välimäki; Lena Schmidt; Jun Xia; Sai Zhao (BMJ Publishing Group, 2022)
Objective To assess the effects of using health social media on different days of the working week on web activity.
Design Individually randomised controlled parallel group superiority trial.
Setting Twitter and Weibo.
Participants 194 Cochrane Schizophrenia Group full reviews with an abstract and plain language summary web page. There were no human participants.
Interventions Three randomly ordered slightly different messages (maximum of 140 characters), each containing a short URL to the freely accessible summary page, were sent on specific times on a single day. Each of these messages sent on Tuesday, Wednesday, Thursday and Friday was compared with the one sent on Monday.
Outcome The primary outcome was visits to the relevant Cochrane summary web page at 1 week. Secondary outcomes were other metrics of web activity at 1 week.
Results There was no evidence that disseminating microblogs on different days of the working week resulted in any differences in target website activity as measured by Google Analytics (n=194, all page views, adjusted ratios of geometric means 0.86 (95% CI 0.63 to 1.18), 0.88 (95% CI 0.64 to 1.21), 0.88 (95% CI 0.65 to 1.21), 0.91 (95% CI 0.66 to 1.24) for Tuesday–Friday, respectively, overall p=0.89). There were consistent findings for all outcomes. However, activity on the review site substantially increased compared with weeks preceding the intervention.
Conclusion There are no clear differences in the effect when 1 weekday is compared with another, but our study suggests that using microblogging social media such as Twitter and Weibo do increase information-seeking behaviour on health. Tweet any day but do Tweet.